Caregiver Reports of Interactions between Children up to 6 Years and Their Family Dog—Implications for Dog Bite Prevention - Arhant, Christine; Beetz, Andrea Martina; Troxler, Josef (Frontiers in Veterinary Science, 2017)
In children up to six years interactions such as interfering with the dog’s resources but also benign behaviors (e.g. petting) commonly precede a bite incident with the family dog. Therefore, the aim of the present study was to explore the development of everyday interactions between children up to six years and their family dogs and whether parents’ attitudes to supervision are related to those interactions. Additionally, we investigated whether behavior of dogs that had lived in the family for longer than the child differed from those that grew up with children. A self-selected sample of caregivers living with a child up to six years and a family dog was surveyed via an online questionnaire (N = 402). Frequency of observed child behaviors directed towards the dog and dog behaviors directed towards the child were scored on a six-point scale (1-never, 6-very often). Data on characteristics of the caregiver, the child and the dog were collected and a section surveying attitudes to supervision of child-dog interactions was included. Additionally, we asked whether the dog already injured the child. Benign child behaviors towards dogs were most frequently reported (mean±S.D.: 4.1±1.2), increased with child age (rs = 0.38, p<0.001) and reached high levels from six month on. Overall, resource-related interactions were relatively infrequent (2.1±1.1). Most common was the dog allowing the child to take objects from its mouth (4.1±1.7). This behavior was more common with older children (rs = 0.37, p<0.001). Reported injuries during resource-related interactions occurred while feeding treats or taking objects from the dog during fetch play. Dogs that had lived in the family for longer than the child showed less affiliative behaviors towards the child (e.g. energetic affiliative: U = -7.171, p<0.001) and more fear-related behaviors (U = -3.581, p<0.001). Finally, the caregivers’ attitudes to supervision were related to all child behaviors (e.g. allow unsafe behaviors – benign child behavior: rs = 0.47, p<0.001). The results of this study underline the need for a dog bite prevention approach directed towards the caregivers very early in the child-dog relationship, taking into account the child’s age and individual needs of the dog.